STRATEGI PEMBANGUNAN INFRASTRUKTUR KAWASAN PERKOTAAN KOTA SATELIT BITTUANG KABUPATEN TANA TORAJA - -, Indrajaya (Jurnal Ilmiah Ecosystem, 2020)
The results of the analysis of the Urban Area Development Strategy of the Bittuang Satellite City Tana Toraja Regency are focused on developing the potential of the Bittuang satellite urban area, developing urban areas that are integrated with the preservation of urban forest areas, developing the functions of economic activities based on environmental ecosystem sustainability, structuring urban public transport routes which is followed by the development of transportation modes of transportation, development of urban infrastructure through sustainable development planning, development of road network infrastructure to support urban area accessibility, control of land use functions to support the provision of urban green space and the involvement of the community in development will minimize social conflicts